2014
DOI: 10.1016/j.nmd.2014.06.435
|View full text |Cite
|
Sign up to set email alerts
|

Progression of muscle histopathology but not of spliceopathy in myotonic dystrophy type 2

Abstract: Myotonic dystrophy type 2 (DM2) is an autosomal dominant progressive disease involving skeletal and cardiac muscle and brain. It is caused by a tetranucleotide repeat within the first intron of the CNBP gene that leads to an alteration of the alternative splicing of several genes. To understand the molecular mechanisms that play a role in DM2 progression, the evolution of skeletal muscle histopathology and biomolecular findings in successive biopsies have been studied. Biceps brachii biopsies from 5 DM2 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Moreover, this study also demonstrated that the affected genes are involved in numerous pathways and networks important for muscle physio-pathology, suggesting that the identified variants may contribute to DM2 pathogenesis [85]. In DM2 patients, symptoms such as muscle weakness and myotonia undergo progressive worsening with increasing age, however, this aggravation is not accompanied by a worsening of alternative splicing of several genes [39]. …”
Section: Myotonic Dystrophy Typementioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, this study also demonstrated that the affected genes are involved in numerous pathways and networks important for muscle physio-pathology, suggesting that the identified variants may contribute to DM2 pathogenesis [85]. In DM2 patients, symptoms such as muscle weakness and myotonia undergo progressive worsening with increasing age, however, this aggravation is not accompanied by a worsening of alternative splicing of several genes [39]. …”
Section: Myotonic Dystrophy Typementioning
confidence: 96%
“…Moreover, in DM2 muscle biopsy central nucleation selectively affects type 2 fibers and the atrophic nuclear clumps express fast myosin isoform (type 2 fiber) indicating that DM2 is predominantly a disease of type 2 myofibers [37]. Recently, Cardani et al [39] have studied the progression of the muscular involvement in relation to the evolution of skeletal muscle histopathology and biomolecular findings to better prognosticate patients with DM2. Data confirm that disease progression in DM2 is slow since histological and biomolecular alterations observed in skeletal muscle are minimal even after a 10-year interval.…”
Section: Myotonic Dystrophy Typementioning
confidence: 99%
See 3 more Smart Citations